Iingoma Zomzabalazo in Conversation: An Archival Engagement with Recordings of Liberation Songs - Ka Dideka, Lukhanyo; Verghese, Ben (Kronos (Bellville, South Africa), 2023)
This text is a remix of an archival engagement with recordings/performances of 'freedom songs' or 'liberation songs' in a south or southern African context. The authors began this collaborative research project as part of a course in the Masters in History degree programme at the University of the Western Cape (UWC). The essay includes a re-edited, updated transcript of dialogue the authors shared along with two mix(tap)es they produced together. The conversation speaks of songs as archives, archives of song(s), and memory/ies pertaining to anti-Apartheid struggle and ongoing Fallism.